Virtually spatialized sounds enhance auditory processing in healthy participants and patients with a disorder of consciousness - Lizette Heine; Alexandra Corneyllie; Florent Gobert; Jacques Luauté; Mathieu Lavandier; Fabien Perrin (Scientific Reports, 2021)
Abstract Neuroscientific and clinical studies on auditory perception often use headphones to limit sound interference. In these conditions, sounds are perceived as internalized because they lack the sound-attributes that normally occur with a sound produced from a point in space around the listener. Without the spatial attention mechanisms that occur with localized sounds, auditory functional assessments could thus be underestimated. We hypothesize that adding virtually externalization and localization cues to sounds through headphones enhance sound discrimination in both healthy participants and patients with a disorder of consciousness (DOC). Hd-EEG was analyzed in 14 healthy participants and 18 patients while they listened to self-relevant and irrelevant stimuli in two forms: diotic (classic sound presentation with an “internalized” feeling) and convolved with a binaural room impulse response (to create an “externalized” feeling). Convolution enhanced the brains’ discriminative response as well as the processing of irrelevant sounds itself, in both healthy participants and DOC patients. For the healthy participants, these effects could be associated with enhanced activation of both the dorsal (where/how) and ventral (what) auditory streams, suggesting that spatial attributes support speech discrimination. Thus, virtually spatialized sounds might “call attention to the outside world” and improve the sensitivity of assessment of brain function in DOC patients.